Performance of village pharmacies and patient compliance after implementation of an essential drug programme in rural Burkina Faso - Krause, Gérard; Benzler, Justus; Heinmüller, Rolf; Borchert, Matthias; Koob, E.; Ouattara, K.; Diesfeld, Hans J. (Health policy and planning, 1998)
After implementation of a nation-wide essential drug programme in Burkina Faso a prospective study was undertaken consisting of non-participant observation in the health centre and in the village pharmacy, and of household interviews with the patients. The study covered all general consultations in nine health centres in three districts over a two-week period as well as all client-vendor contacts in the corresponding village pharmacies; comprising 313 patients in consultations and 498 clients in eight village pharmacies with 12 vendors involved in dispensing 908 drugs. Additionally patients were interviewed in their households. Performance and utilization of the village pharmacy: 82.0% of the drugs prescribed in the health centres were actually dispensed at the village pharmacy; 5.9% of the drugs were not available at the village pharmacy. Wrong drugs were dispensed in 2.1% of cases. 41.3% of the drugs dispensed in the village pharmacy were bought without a prescription. Differences are seen between the districts and are put in relation to different onset of the essential drug programme.Patient compliance: Patients could recall the correct dosage for 68.3% of the drugs. Drug taking compliance was 63.1%, derived from the pills remaining in the households. 11.5% of the drugs had obviously been taken incorrectly to such an extent that the occurrence of undesired drug effects was likely.The study demonstrates the success of the essential drug programme not only in performance but also in acceptability and utilization by the population.
Gesehen am 24.10.2024